Stereotype threat, trait perseveration, and vagal activity: evidence for mechanisms underpinning health disparities in Black Americans. Issue 8 (17th November 2019) - Williams, DeWayne P.; Joseph, Nicholas; Hill, LaBarron K.; Sollers, John J.; Vasey, Michael W.; Way, Baldwin M.; Koenig, Julian; Thayer, Julian F.
ABSTRACT: Objective: Black Americans (BAs) are at an elevated risk for morbidity and mortality in comparison to White Americans (WAs). Racial stressors are a common occurrence in American culture and is theorized to contribute to these disparities. When race-focused, stereotype threat (ST) is considered to be a factor that is detrimental to health in BAs; however few studies have directly investigated the impact of a ST manipulation on physiological function. Furthermore, it is proposed that racial stressors such as ST may have prolonged effects when more likely to perseverate (e.g. rumination) over the stressor and thus, those with greater trait perseveration may be more affected by ST. We sought to explore the impact of ST and trait perseveration on changes in vagus nerve activity – an indication of adaptive psychological and physiological well-being – as indexed by vagally mediated heart rate variability (vmHRV). Design: Forty-three (24 females, mean age of 20, standard deviation of 3 years) apparently healthy BA individuals were randomly assigned to one of three experimental conditions in which they received either implicit (subtle), explicit (blatant), or no ST priming (control condition), prior to completing a cognitive task. Resting vmHRV was assessed both at baseline (pre-task) and recovery (post-task). Results: BAs in the explicit ST condition exhibited the greatest decrease in vmHRV in comparison to the control group from pre- to post-task. BAs with moderate to high levels of trait perseveration showed the greatest decrease in vmHRV from pre- to post-task in comparison to those with lower levels of trait perseveration and BAs in the control group. Conclusion: These data suggest that racial ST, especially when explicit and coupled with trait perseveration, can decrease vagal activity, as indexed by decreased vmHRV, which when experienced frequently can have significant consequences for health and longevity in BAs.